Digital Technologies in Supply Chain Management for Production and Digital Economy Development - Aleksandr Amiranovich Kartskhiya; Sergey Anatolyevich Tyrtychnyy; Mikhail Guramovich Smirnov; Mariya Gennadyevna Dolgikh; Leonid Aleksandrovich Khmelnitskiy (International Journal of Supply Chain Management, 2020)
Abstract- the paper analyzes the development of digital technology and the establishment of blockchain systems in the supply chain management for digital economy development. We examined how blockchain is likely to affect key supply chain management objectives such as cost, quality, speed, dependability, risk reduction, sustainability and flexibility. The authors attempt to classify different kinds of tokens and explain the terminology related to cryptocurrencies. They analyze the economic development of tokens and legal regulation surrounding their usage in supply chain. The study revealed the advantages of using digital technlogies in supply chain management over traditional business management technologies and logistics systems, especially in covid-19 conditions.